2015
DOI: 10.1128/cvi.00116-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the HISCL Anti-Treponema pallidum Assay as a Screening Test for Syphilis

Abstract: The resurgence of syphilis in recent years has become a serious threat to public health worldwide, and the serological detection of specific antibodies against Treponema pallidum remains the most reliable method for laboratory diagnosis of syphilis. This study examined the performance of the recently launched HISCL anti-Treponema pallidum (anti-TP) assay as a screening test for syphilis in a high-volume laboratory. The HISCL anti-TP assay was tested in 300 preselected syphilis-positive samples, 704 fresh syphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…et al (16) screened 13,767 serum samples from 13 centers in China and obtained a sensitivity of 100% and a specificity of 99.81% for Elecsys in detecting anti-TP. Similar data on sensitivity and specificity of HISCL was reported by An et al(17). Elecsys anti-HCV II assay showed a sensitivity of 100% and a specificity of 99.66% in 7,726 routine samples from the Asia-Pacific region(18), while research by Feng et al(19) revealed that HISCL anti-HCV assay had a sensitivity of 98.97% and specificity of 100% in 1,048 samples from China.…”
supporting
confidence: 75%
“…et al (16) screened 13,767 serum samples from 13 centers in China and obtained a sensitivity of 100% and a specificity of 99.81% for Elecsys in detecting anti-TP. Similar data on sensitivity and specificity of HISCL was reported by An et al(17). Elecsys anti-HCV II assay showed a sensitivity of 100% and a specificity of 99.66% in 7,726 routine samples from the Asia-Pacific region(18), while research by Feng et al(19) revealed that HISCL anti-HCV assay had a sensitivity of 98.97% and specificity of 100% in 1,048 samples from China.…”
supporting
confidence: 75%
“…The automated Lumipulse G TP-N assay was cleared in July 2016 by the U.S. Food and Drug Administration (FDA) as an aid in the diagnosis of syphilis. To our knowledge, this is the only study comparing the Lumipulse G TP-N assay to another automated, FDA-cleared assay (17)(18)(19). A total of 4,034 serum samples routinely submitted for syphilis screening and samples from 100 high-risk HIV patients were tested by the Lumipulse G TP-N assay and the Bioplex 2200 Syphilis IgG assay.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this may be the first report of a patient with syphilitic femoral artery aneurysm who was successfully treated by combined open and endovascular repair. However, this study has some limitations, such as the shorter follow-up time, the treponeme not identified in the removed tissues, and the syphilis confirmed only by RPR and Treponema pallidum hemagglutination antibody assay, not including other tests, such as venereal disease research laboratory (VDRL), treponemal pallidum particle agglutination (TPPA), fluorescence test assay absorption (FTA-ABS), the enzyme immunoassay (EIA) or the chemiluminescent immunoassay (CLIA) [ 21 ]. Thus, case series studies are needed to provide the systematic diagnosis and treatment recommendation for syphilitic femoral artery aneurysm.…”
Section: Discussionmentioning
confidence: 99%